A Nd:Yag Pumped Binary Laser Dye Mixture for the 397-427 Nm Wavelength Region. Issue 1 (1994) - French, J. L.; Karolczak, J.; Clouthier, Dennis J.
Abstract : A useful mixture of the laser dyes DPS and bis-MSB in a 9:1 dioxane and methanol solution is described. The binary dye system exhibits broad tunability, symmetric degradation and reasonable conversion efficiency with 355 nm Nd:YAG pumping.